Discovery of the novel autophagy inhibitor aumitin that targets mitochondrial complex I. Issue 11 (26th February 2018) - Robke, Lucas; Futamura, Yushi; Konstantinidis, Georgios; Wilke, Julian; Aono, Harumi; Mahmoud, Zhwan; Watanabe, Nobumoto; Wu, Yao-Wen; Osada, Hiroyuki; Laraia, Luca; Waldmann, Herbert
Abstract : Phenotypic screening for autophagy inhibitors followed by target identification resulted in the discovery of aumitin, a new autophagy inhibitor that inhibits mitochondrial respiration by targeting complex I. Abstract : Macroautophagy is a conserved eukaryotic process for degradation of cellular components in response to lack of nutrients. It is involved in the development of diseases, notably cancer and neurological disorders including Parkinson's disease. Small molecule autophagy modulators have proven to be valuable tools to dissect and interrogate this crucial metabolic pathway and are in high demand. Phenotypic screening for autophagy inhibitors led to the discovery of the novel autophagy inhibitor aumitin. Target identification and confirmation revealed that aumitin inhibits mitochondrial respiration by targeting complex I. We show that inhibition of autophagy by impairment of mitochondrial respiration is general for several mitochondrial inhibitors that target different mitochondrial complexes. Our findings highlight the importance of mitochondrial respiration for autophagy regulation.